Small-scale irrigation potential in Sub-Saharan Africa: Targeting investments in technologies, locations and institutions - Koo, Jawoo; Olayide, Olawale; Sangaré, Saadatou (Center for Development Research, Germany, 2019)
The limited access to water the during dry season or a drought greatly restricts farming opportunities and productivity increases in Sub-Saharan Africa. Irrigation can thus be a promising solution to boost levels of agricultural productivity. However, only about 4% of land in the region is irrigated. This is not necessarily due to physical water scarcity. Rather, the main constraint of irrigation is economic water scarcity, i.e. investments in the management of water resources are not substantial enough to meet water demand and farmers do not have the financial means to exploit water resources on their own. Research has shown that small-scale irrigation systems can help adress this economic water scarcity in Africa.